The effect of learning questioning and answering (RQA) based practicum model on learning outcome in the plant world material at MAN Kota Banda Aceh - Erna Diana; Hasanuddin Hasanuddin; Abdullah Abdullah (Jurnal Edubio Tropika, 2018)
This study aims to determine the effect of the use of RQA-based learning model of the practicum on the learning outcomes in the material world of plants. Data retrieval conducted in February 2017. The method used in this research is the Quasi Experiment method. This research conducted at three State Madrasah Aliyah (MAN) of Banda Aceh city that is MAN 1 class X IPA 3 as experiment class and X IPA 4 as control class, MAN 2 class X MIA 3 as experiment class and X MIA 1 as control class, MAN 3 class X MIA 1 as experiment class and X MIA 2 as control class. The instruments used were the test of learning outcomes using multiple choice test questions. Data analysis is using variance analysis (ANAVA) at significant level 0,05. The result of variance analysis shows that F count F table is for learning outcomes was 182,042,26. The conclusion of the RQA learning model based on the Practicum influenced the learning outcomes of learners on the material world of plants in MAN Kota Banda Aceh.Keywords: Reading Questioning and Answering, Practicum and Learning Outcomes.